The dependence of preferred competitive racing distance on muscle fibre type composition and ACTN3 genotype in speed skaters - Ahmetov, I. I.; Druzhevskaya, A. M.; Lyubaeva, E. V.; Popov, D. V.; Vinogradova, O. L.; Williams, A. G. (Experimental Physiology, 2011)
It is generally accepted that muscle fibre composition may influence physical performance. The a-actinin-3 (ACTN3) gene R577X polymorphism is suspected to be one of the contributing gene variations in the determination of muscle fibre type composition and athletic status. In the present study, we examined the dependence of average preferred racing distance (PRD) on muscle fibre type composition of the vastus lateralis muscle in 34 subelite Russian speed skaters (20 men and 14 women) who competed in races of different length (500-10,000 m). We also investigated the association between the ACTN3 polymorphism and muscle fibre characteristics in 94 subjects (60 physically active healthy men and 34 speed skaters), as well as the relationship between PRD and ACTN3 genotype in 115 subelite and elite speed skaters. In addition, ACTN3 genotype and allele frequencies of the 115 speed skaters were compared with 1301 control subjects. The ACTN3 XX genotype frequency was significantly lower in sprinters (n = 39) compared with control subjects (2.6 versus 14.5%; P = 0.034). We observed a positive relationship between PRD and the proportion of slow-twitch muscle fibres that was close to linear, but better fitted a logarithmic curve (r = 0.593, P < 0.0005). The ACTN3 R577X polymorphism was associated with muscle fibre composition (slow-twitch fibres: RR genotype, 51.7 (12.8)%; RX, 57.4 (13.2)%; XX 61.5 (16.3)%; p = 0.215; P = 0.049) in the overall muscle biopsy group, and with PRD of all athletes (? = 0.24, P = 0.010), indicating that ACTN3 XX genotype carriers exhibit a higher proportion of slow-twitch fibres and prefer to skate long-distance races. However, the majority of the association between muscle fibre type and PRD was independent of ACTN3 genotype. In conclusion, the ACTN3 R577X polymorphism is associated with preferred racing distance in speed skaters and muscle fibre type composition. Thus, it is probably partly via associations with fibre type that the R577X polymorphism contributes to a small but perhaps important component of the ability to perform at a high level in speed skating.